Obesity-related insulin resistance in adolescents: a systematic review and meta-analysis of observational studies. (4th March 2017) - Thota, P.; Perez-Lopez, F. R.; Benites-Zapata, V. A.; Pasupuleti, V.; Hernandez, A. V.
Abstract: Insulin resistance is common among obese adolescents; however, the extent of this problem is not clear. We conducted a systematic review of PubMed-Medline, CINAHL, The Web of Science, EMBASE and Scopus for observational studies evaluating components defining insulin resistance (insulin, C-peptide and homeostatic model assessment-insulin resistance [HOMA-IR]) in obese adolescents (12–18 years) versus non-obese adolescents. Our systematic review and meta-analysis followed the PRISMA guidelines. Data were combined using a random-effects model and summary statistics were calculated using the mean differences (MDs). 31 studies were included ( n = 8655). In 26 studies, fasting insulin levels were higher in obese adolescents when compared to non-obese adolescents (MD = 64.11 pmol/L, 95%CI 49.48–78.75, p < 0.00001). In three studies, fasting C-peptide levels were higher in obese adolescents when compared to non-obese adolescents (MD = 0.29 nmol/L, 95%CI 0.22–0.36, p < 0.00001). In 24 studies, HOMA-IR values were higher in obese adolescents when compared to non-obese adolescents (MD = 2.22, 95%CI 1.78–2.67, p < 0.00001). Heterogeneity of effects among studies was moderate to high. Subgroup analyses showed similar results to the main analyses. Circulating insulin and C-peptide levels and HOMA-IR values were significantly higher in obese adolescents compared to those non-obese.